Acne in Klinefelter syndrome-46XY/47XXY mosaicism? - Chembolli Lakshmi; Selvaraj Swarnalakshimi (Wolters Kluwer Medknow Publications, 2015)
Klinefelter syndrome (KFS) is the most common non-heritable sex chromosome anomaly caused by nondisjunction during cell division and contains two or more X chromosomes. More than two third of all cases are homogenous (47XXY) and the remaining are mosaic (46XY/47XXY). Lower limb ulcers are frequently observed and attributed to impaired fibrinolysis. A case of KFS with post acne scars and leg ulcers is presented. The rarity of acne in this syndrome is explained by the phenomenon of mosaicism.